PENGARUH KNOWLEDGE SHARING, HUMAN RELATION , DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA PT. SUMATERA TROPICAL SPICES - Riri Mayliza; Gilang Gilang (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this research is to examine the influence of the variables knowledge sharing, human relations and work enthusiasm on employee perfomance PT. Sumatera Tropical Spices. This type of research uses quantitative methods, collecting data through distributing questionnaires to 118 respondents using total sampling. By using instrument testing (validity test and reliability test), classic assumption tests (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of the SPSS application. The results of the research show that knowledge sharing has a positive and significant effect on employee perfomance, human relations has a positive and significant effect on employee perfomance, and work morale has a positive and significant effect on employee perfomance